Ovarian dysfunction in women with Turner syndrome - Fukami, Maki (Frontiers in Endocrinology, 2023)
Ovarian dysfunction is one of the most common features of women with Turner syndrome. In these women, oocyte apoptosis is markedly accelerated from the early stage of fetal life. Reduction in the number of germ cells disturbs primordial follicle formation and thereby leads to the formation of streak gonads. There are three possible causes of accelerated germ cell loss in 45,X ovaries. First, chromosomal pairing failure due to X chromosomal aneuploidy is believed to induce meiotic arrest. Indeed, it has been suggested that the dosage of the X chromosome is more critical for the survival of the oocytes than for other cells in the ovary. Second, impaired coupling between oocytes and granulosa cells may also contribute to germ cell apoptosis. Previous studies have shown that 45,X ovaries may tend to lose tight junctions which are essential for intercellular interactions. Lastly, ovarian dysfunction in women with Turner syndrome is partly attributable to the reduced dosage of several genes on the X chromosome. Specifically, BMP15, PGRMC1, and some other genes on the X chromosome have been implicated in ovarian function. Further studies on the mechanisms of ovarian dysfunction are necessary to improve the reproductive outcomes of women with Turner syndrome.